Tenure and street-level bureaucrats: How assessment tools are used at the frontline of the public sector - Anahita Assadi; Martin Lundin (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2015)
The tension between governance and professional discretion is a question of constant interest in public administration research, and studies on street-level bureaucracy thus aim to understand the actions of frontline workers. Largely missing in this literature, however, is research on how tenure affects behavior. To fill in this gap, we analyze how caseworkers with varying degrees of tenure respond to steering signals. We study the nationwide introduction of an assessment support tool to be used to assess clients' needs under the Swedish active labor market policy. We propose that accumulated experiences strengthen frontline workers' confidence. In turn, this makes them less responsive to formal policy signals, such as the assessment tool. Qualitative and quantitative methods are both used in support of the current research. The analysis suggests that as tenure increases, street-level bureaucrats, especially male caseworkers, tend to use the assessment tool less carefully and act in accordance with policy signals to a lesser extent. The qualitative analysis indicates that this pattern can partly be explained by the fact that increasing experience with meeting clients face-to-face increases caseworkers' perceived skills and confidence.
Keywords: J20; 330; street-level bureaucracy; policy implementation; discretion; tenure; assessment support tool; profiling; active labor market policy